Immunotoxic effects of single and combined pharmaceuticals exposure on a harbor seal (Phoca vitulina) B lymphoma cell line. Issue 1 (15th May 2017) - Kleinert, Christine; Lacaze, Emilie; Mounier, Méryl; De Guise, Sylvain; Fournier, Michel
Abstract: The potential risk of pharmaceuticals in the environment to top-predators is still largely unknown. In this study, we assessed the immunotoxic effects of ten pharmaceuticals individually and as mixtures on a harbor seal ( Phoca vitulina ) B lymphoma cell line. A significant reduction in lymphocyte transformation was observed following an exposure to 12, 500 μg/L 17α-ethinyl estradiol and 25, 000 μg/L naproxen. Exposure to 12, 500 μg/L 17α-ethinyl estradiol decreased the percentage of cell in the G0 /G1 phase of the cell cycle while increasing the percentage of cells in the S phase. Carbamazepine exposure increased the amount of cells in the G2 /M phase. Binary mixtures showed synergistic effects in lymphocyte transformation, cell cycle and apoptosis assays. Concentrations inducing toxic effects in the cell line were similar to those affecting fish in previous studies. A reduction of functional activities of the immune system may lead to altered host resistance to pathogens in free-ranging pinnipeds. Graphical abstract: Highlights: First study of the immunotoxicity of pharmaceutical products in a marine mammal cell line. 17α-ethinyl estradiol and naproxen inhibited the seal immune cell line's proliferative response. 17α-ethinyl estradiol and carbamazepine influenced the cell cycle of the seal B lymphoma cell line. Mixtures of pharmaceuticals were found to be more immunotoxic than single compounds.